Ride to the bullet [large type] - Dundee, Wayne D. (Dundee, Wayne D., Lone McGantry western, 2025)
"Eight months into rebuilding his abandoned horse ranch, former Indian Scout Lone McGantry's world takes a treacherous turn when he comes to the aid of ex-outlaw Wade Avril. Fending off three vengeful gang members from Wade's past, Lone unwittingly draws the ire of gang leader Pike Grogan. With a bounty on Wade's head, the duo decides to confront the menace at its source: Pike's hideout in North Dakota. As they navigate a landscape fraught with bounty hunters, old grudges, and unexpected challenges, their quest for justice becomes a bloody fight for survival. Along the way, they'll discover the true cost of redemption in a land where danger lurks at every turn, testing their mettle and redefining the boundaries of vengeance."--